Low-frequency wide band-gap elastic/acoustic metamaterials using the K-damping concept - Antoniadis, I.; Chatzi, E.; Chronopoulos, Dimitrios; Paradeisiotis, A.; Sapountzakis, I.; Konstantopoulos, S. (2017)
The terms “acoustic/elastic meta-materials” describe a class of periodic structures with unit cells exhibiting local resonance. This localized resonant structure has been shown to result in negative effective stiffness and/or mass at frequency ranges close to these local resonances. As a result, these structures present unusual wave propagation properties at wavelengths well below the regime corresponding to band-gap generation based on spatial periodicity, (i.e. “Bragg scattering”). Therefore, acoustic/elastic meta-materials can lead to applications, especially suitable in the low-frequency range. However, low frequency range applications of such meta-materials require very heavy internal moving masses, as well as additional constraints at the amplitudes of the internally oscillating locally resonating structures, which may prohibit their practical implementation. In order to resolve this disadvantage, the KDamping concept will be analyzed. According to this concept, the acoustic/elastic meta-materials are designed to include negative stiffness elements instead or in addition to the internally resonating added masses. This concept removes the need for the heavy locally added heavy masses, while it simultaneously exploits the negative stiffness damping phenomenon. Application of both Bloch’s theory and the classical modal analysis at the one-dimensional mass-in-mass lattice is analyzed and corresponding dispersion relations are derived. The results indicate significant advantages over the conventional mass-in-a mass lattice, such as broader band-gaps and increased damping ratio and reveal significant potential in the proposed solution. Preliminary feasibility analysis for seismic meta-structures and low frequency acoustic isolation-damping confirm the strong potential and applicability of this concept.